Fluid–structure–sound interaction in noise reduction of a circular cylinder with flexible splitter plate. (4th June 2021) - Duan, Fan; Wang, Jinjun
Abstract: Abstract : The fluid–structure--sound interaction in reducing the flow-induced noise of a circular cylinder with a back flexible splitter plate is investigated experimentally. The rigid splitter plate (RSP) and the flexible splitter plate (FSP) are individually attached to the rear of the cylinder with a diameter D = 30 mm. Three parameters are considered: the flexibility of the plates, the length of the plates ( L = 0.5 D ~ 6.0 D ) and the Reynolds numbers ( Re = 3.83×10 4 ~ 9.57 × 10 4 ). Both RSP and FSP achieve the optimal reduction in the Aeolian tone at L/D = 1.0 regardless of Re, where the RSP results in a reduction of 14 dB on average and the FSP a superior reduction of 18 dB. Subsequently, the velocity fields are measured with two-dimensional particle image velocimetry for L/D = 1.0. The dynamic deformation of the FSP is captured with a single-camera three-dimensional digital image correlation system. The results show that the splitter plate elongates the recirculation region length ( Lr ) significantly, and it is preferable to normalize the streamwise coordinate x with Lr instead of D in this investigation. It is determined that the Aeolian tone is mainly induced by the fluctuations in the near wake region of 1 < x/Lr < 3. The splitter plates effectively suppress the overall fluctuations originating from vortex shedding in the wake, thereby reducing the Aeolian tone successfully. The movement of the FSP, which is dominated by low-frequency vibrations with broadband and a relatively energetic periodic vibration, has important effects on the secondary and high-frequency noise.